Plasmin and Matrix Metalloproteinases in Vascular Remodeling - Lijnen, H. R. (Thrombosis and Haemostasis, 2001)
Vascular remodeling, defined as lasting structural changes in the vessel wall in response to hemodynamic stimuli, plays a role in many (patho)physiological processes requiring cell migration and degradation of extracellular matrix (ECM). Two proteolytic systems, the fibrinolytic (plasminogen/plasmin) and matrix metalloproteinase (MMP) systems can degrade most ECM components. The availability of mice models with deficiency of main components of both systems has allowed to study their contribution to vascular remodeling in several biological processes. In mouse models of atherosclerosis, urokinase-mediated plasmin generation plays a role in activation of several macrophage-derived MMPs (MMP-3, -9, -12 and -13), triggering elastolysis and collagenolysis, resulting in media destruction and aneurysm formation. Neointima formation after vascular injury, a process that depends on smooth muscle cell migration, is reduced in mice with plasminogen or urokinase deficiency and enhanced in mice with deficiency of TIMP-1 (type 1 tissue inhibitor of MMPs). Also in allograft transplant arteriosclerosis and in abdominal aortic aneurysm both proteolytic systems contribute to matrix degradation. In a mouse model of myocardial infarction, urokinase deficiency protects totally and MMP-9 deficiency partially against cardiac rupture, but these animals suffer cardiac failure. Thus, the plasminogen/plasmin and MMP systems, in concert, contribute to vascular remodeling in the setting of cardiovascular disease.
Keywords: Fibrinolysis; matrix metalloproteinases; vascular remodeling; cardiovascular disease